Combined use of stable isotopes and hydrochemical characteristics to determine streamflow sources in the Jonkershoek catchment, South Africa. Issue 3 (3rd May 2020) - Mokua, Retang A.; Glenday, Julia; Nel, Jacobus; Butler, Mike
ABSTRACT: The stable isotopes of water ( 18 O, 2 H) and other hydrochemical properties were used to assess seasonal changes between sources of stream water and flow pathways in baseflow conditions for two headwater sub-catchments (∼3 km 2 ) of the Jonkershoek, a mountainous catchment in the Western Cape of South Africa. The sub-catchments differ in land cover, one is dominated by indigenous fynbos vegetation and the other by pine plantation. Stream water, higher elevation springs, and lower elevation groundwater samples were collected monthly from January 2018 to January 2019, and were analysed for stable isotopes, electrical conductivity (EC) and pH. The stream water isotopic values resembled those of groundwater during the dry and wet seasons. Results indicated a steady contribution of spring discharge to streams during the dry season, with rainfall contribution less evident. Wet season flows were attributed to interflow including perennial and ephemeral springs. Spatial variations in EC between the sub-catchments were indicative of a greater proportional input from subsurface water, more evaporation and/or more mineral dissolution in the pine-dominated sub-catchment. The spatiotemporal variability in EC was significantly larger than for the stable isotopes. These findings enabled conceptualization of streamflow generation processes that can support strategic water resource management practices in this region.